Conservation of Epithelial-to-Mesenchymal Transition Process in Neural Crest Cells and Metastatic Cancer - Zhang, April; Aslam, Hira; Sharma, Neha; Warmflash, Aryeh; Fakhouri, Walid D (Cells, tissues, organs, 2021)
Epithelial to mesenchymal transition (EMT) is a highly conserved cellular process in several species, from worms to humans. EMT plays a fundamental role in early embryogenesis, wound healing, and cancer metastasis. For neural crest cell (NCC) development, EMT typically results in forming a migratory and potent cell population that generates a wide variety of cell and tissue, including cartilage, bone, connective tissue, endocrine cells, neurons, and glia amongst many others. The degree of conservation between the signaling pathways that regulate EMT during development and metastatic cancer (MC) has not been fully established, despite ample studies. This systematic review and meta-analysis dissects the major signaling pathways involved in EMT of NCC development and MC to unravel the similarities and differences. While the FGF, TGFβ/BMP, SHH, and NOTCH pathways have been rigorously investigated in both systems, the EGF, IGF, HIPPO, Factor Receptor Superfamily, and their intracellular signaling cascades need to be the focus of future NCC studies. In general, meta-analyses of the associated signaling pathways show a significant number of overlapping genes (particularly ligands, transcription regulators, and targeted cadherins) involved in each signaling pathway of both systems without stratification by body segments and cancer type. Lack of stratification makes it difficult to meaningfully evaluate the intracellular downstream effectors of each signaling pathway. Finally, pediatric neuroblastoma and melanoma are NCC-derived malignancies, which emphasize the importance of uncovering the EMT events that convert NCC into treatment-resistant malignant cells.